2005
DOI: 10.1073/pnas.0408071102
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics and quasichemical study of H + (aq)

Abstract: The excess proton in water, H ؉ (aq), plays a fundamental role in aqueous solution chemistry. Its solution thermodynamic properties are essential to molecular descriptions of that chemistry and for validation of dynamical calculations. Within the quasichemical theory of solutions those thermodynamic properties are conditional on recognizing underlying solution structures. The quasichemical treatment identifies H 3O ؉ and H2O5 ؉ as natural innershell complexes, corresponding to the cases of n ‫؍‬ 1, 2 water mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
99
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 40 publications
6
99
1
Order By: Relevance
“…35 Recently, using CPMD combined with transition path sampling, [36][37][38] it was shown 1 that the transfer of a proton in the O-H‚‚‚O system represents a first step and that the dissociation of O-H bonds is driven by the concerted changes in the electric field and in the hydrogen-bond network. Despite extensive studies employing different theoretical approaches, 26,35,[39][40][41][42][43] the detailed mechanism of proton transfer is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recently, using CPMD combined with transition path sampling, [36][37][38] it was shown 1 that the transfer of a proton in the O-H‚‚‚O system represents a first step and that the dissociation of O-H bonds is driven by the concerted changes in the electric field and in the hydrogen-bond network. Despite extensive studies employing different theoretical approaches, 26,35,[39][40][41][42][43] the detailed mechanism of proton transfer is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature and, more specifically, the thermodynamical state of the system plays a central role both on structure and location of the proton species and also on dynamics of the proton transfer. Whereas plenty of information about PT in liquid water and in biomolecular systems at ambient conditions is available [9][10][11][12][13][14][15][16][17][18][19][20][21][22], its characteristics at low temperatures, such as in supercooled states, for the wide variety of ice * jordi.marti@upc.edu classes and for high-and low-density amorphous ices (LDA) is still largely unknown. Given the complexity of the phase diagram of water [23,24], studies of structure and dynamics of aqueous lone protons are usually reported for restricted regions of the diagram.…”
Section: Introductionmentioning
confidence: 99%
“…At ambient conditions, plenty of information about PT in liquid water and in biomolecular systems at ambient conditions is available. [2,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Far from ambient conditions, it has been observed that rates of PT and diffusion coefficients of the proton show marked variations from room temperature values, when a wide range of states (from supercooled to supercritical) have been explored. [22][23][24][25] When confined in constrained geometries, the microscopical properties of the proton also suffer drastic changes.…”
Section: Introductionmentioning
confidence: 99%